The Holocene history of the Guadiana estuary as told by diatoms and chrysophyte cysts - Gomes, A.I. (2015)
In order to tell the history of the Guadiana Estuary since the Last Glacial Maximum, a core collected therein, and spanning more than 13200 cal. years B.P., was studied regarding its diatom and chrysophyte cyst fossil records. Additionally, a diatom-based transfer function was used to reconstruct paleo-salinity and paleo-duration of tidal inundation to better understand the estuary’s evolution in relation to sea-level rise and climate changes. This study identifies some important climatic events, such as the Allerød climatic optimum, the Younger Dryas and three dry and cold events at 10600, 9100 and 7600 cal. years B.P., most of which were not identified by other proxies. Moreover, it also revealed that, prior to 13200 cal. years B.P., there was a mudflat environment in the place where the core was collected, consistent with an estuary slightly confined in the narrow valley under marine/tidal influence. Afterwards, this environment evolved into a salt marsh. The strongest marine influence was inferred to the period between 10000 and 7000 cal. years B.P., embracing a phase of rapid sea-level rise, non compensated by sedimentation, that favored the development of a mudflat. From this period onwards, diatom assemblages seem to indicate an evolution to a more enclosed environment, probably similar to the actual configuration of the area.